The Diagnosis and Management of Bladder Cancer: A Literature Review - Ikhwan, Haznur; Dahril; Ismy, Jufriady; Ridha, Muhammad; Mauny, Muhammad Puteh; Khalilullah, Said Alfin; Triyaka, Rendy; Maulana, Reza; Hidayatullah, Furqan (International Journal of Public Health Excellence (IJPHE), 2024)
Cancer is still one of the health problems around the world. Cancer is an uncontrolled (abnormal) cell division and can invade surrounding tissues and can also spread to other parts of the body through the blood and lymphatic system known as metastasis. This disease is often diagnosed in men aged 50-80 years with an average age of 73 years. Bladder cancer is divided into transitional cell carcinoma (95%), squamous cell carcinoma (3%), adenocarcinoma (2%), and less than 1% small cell tumors (paraneoplastic syndrome). Risk factors for this disease are smoking, exposure to carcinogenic substances, drugs, infection with the parasite Schistosoma haematobium, chronic irritation (stone disease), physical trauma (in the uroepithelial layer), infectious diseases and those that have not been proven to be the cause are coffee, alcohol, saccharin and cyclamate sweeteners. The prognosis of the disease depends on histologic examination to see the stage of the disease and by tissue biopsy. Methods: This paper is based on a literature search of clinical practice guidelines, scientific literature, websites, and textbooks on the topic of bladder cancer. Results and Discussion: Hematuria is the main clinical symptom in addition to other symptoms as a complaint of bladder cancer. The disease is divided into non-muscle-invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC). Non-invasive and invasive cancer conditions play an important role in the treatment and prognosis of the disease. MIBC is a disease condition with high morbidity and mortality. Conclusion: Cystoscopy followed by biopsy resection is the diagnostic standard followed by anatomic pathology examination (histology and cytology) for definitive diagnosis of the disease. The prognosis will be better if the disease is still at superficial and non-invasive stage (Ta), so that only transurethral tumor resection followed by chemotherapy drugs, intravesical and results will be more satisfactory.